O papel da determinação descendente no julgamento moral ou regulação top-down das emoções morais - Ramos, Marlos Vinícius Oliveira (2019)
The debate concerning human morality has always awoken great interest in the area of philosophy. From the most ancient and classical discussions put forward by Plato, Aristotle and the Hellenist philosophers, the history of philosophical thought has never known a period in which the debates concerning ethics and morality have not been part of their innermost circle. An example of such is the use of the most diverse terminologies for the designation of the innumerous current theories in contemporaneity, such as contractualism, utilitarianism, deontology and metaethics. A large part of philosophical content that permeates through this debate involves a set of normative and prescriptive theses, which as a common theme, propose the discussion of norms or moral judgments, and assembled for the analysis of moral facts and the discrimination of guidelines to access possible solutions to problems involving moral questions and/or dilemmas. Without disregarding the importance of the philosophical knowledge possessed by the researchers of ethics, the present work is situated in another conceptual, methodological and structural paradigm, where it places less concern on prescriptions and norms and more on the philosophical analysis of knowledge, facts and conclusions about the structure, origin and limitations of our moral cognitive thoughts. In this paradigmatic context, we place the theoretical and structural focus on the human decision-making process, and as such analyze the central aspects of moral cognition in the perspective of the philosophy of the mind with the interdisciplinary collaboration of biology, physics, psychology, etc. and in particular the empirical studies of neuroscience. The study outlined herein defends the thesis that the set of human moral principles is derived from cognitive processes that emerge from the physical world, human evolutionary biology and the cultural evolution of our society, which compromises research with an empirical and naturalistic philosophical model. Based upon this theoretical, conceptual, structural and methodological framework, the approach we profess is opposed to some other theoretical approaches, notably Cartesian dualism and physicalism reductionism. The first of these, Cartesian dualism, is opposed to the main theoretical perspective that we will defend in this dissertation, philosophical emergentism, since the emergentist defends the thesis that everything that exists in nature, substances, organisms, organizations, etc. are composed of essentially physical substances. The second approach that we consider distant from ours, is that professed by reductionists, this usually excludes the dialogue between philosophy and science, reducing mental states to types of neural states, or even mental events to physical events, and from which the thesis that mental states can be reduced to neural states is rendered. By taking into consideration these fundamental factors, this dissertation is supported on three basic pillars, namely: (a) there are natural biological factors of morality that condition moral cognition to a naturalistic and evolutionary explanation; (b) there is a predominant role of moral emotions in conditioning the automatic and instinctive reactions of human behavior; (c) there is a role of descending determination or top-down regulation of moral emotions, in the ability to restrain and repress automatic behaviors of moral decision-making. From these three principles that guide our Dissertation, we consider it plausible to maintain that moral cognition can be understood as a set of cognitive mechanisms that emerge from neurophysiological processes primarily composed of automatic behaviors, supported by nonconscious instinctive reactions, and which are capable of being consciously operated by means of a descending / top-down regulation process. The authors of this paper believe that these cognitive mechanisms have human survival as their main goal, be that on an individual level or of a particular group of individuals. From this conceptual definition we arrive at the central thesis of this study, which is that the mechanisms that support deliberate and conscious decisions are capable of promoting the descending determination or top-down regulation of moral emotions. This structural dynamic enables human beings, unlike beings of lower levels of development, to produce more complex and evolved behaviors capable of controlling the most basic reflexes of self-preservation in a deliberate manner from rational reflection, through conscious mental mechanisms and processes.